Waste heat recovery at low temperature from heat pumps, power cycles and integrated systems – Review on system performance and environmental perspectives. (August 2022) - Nandhini, Rajendran; Sivaprakash, Baskaran; Rajamohan, Natarajan
Abstract: Utilization of unused waste heat energy below 100 °C is a challenging effort. In spite of investing in energy retrieving technology, a considerable amount of heat energy is still dissipating to the surroundings. The recovery of LTWH through different technologies plays a pivotal role in several process industries and domicile application. Heat pumps are widely employed to retrieve low level heat energy and also aid in reducing greenhouse gas emission. Hybrid absorption-compression heat pump showed maximum of 95% waste heat recovery rate, where air-source and CO2 trans critical heat pump reduced energy consumption by 60–75% and centrifugal heat pumps generated 9700 kW capacity of heat. Most of the studies reported the effective performance of absorption heat pump units with heat source temperature lie in the range of 60–120 °C along with maximum energy and exergy production with minor irreversible energy loss. Nanofluids are emerging as a high-performance working fluid for heating and cooling applications. Silver/pentane nanofluids increased overall system efficiency and showed 14% less carbon footprint, which is considered as a most effective alternate to hazardous working fluids. The simultaneous production of potable water and electrical power generation through desalination system was reviewed. The techno-economic assessment of using heat pumps in low grade energy recovery and its integrated prototype were presented in this paper together with the environmental impact of working fluids used in the heat pumps and thermodynamic cycles.